Heavy metal Mater and other tall tales - Berrios, Frank; Disney Enterprises (1996- ); Pixar (Firm) (New York : Random House, 2010)
A collection of three stories featuring Mater who tells Lightning McQueen how he started a rock band, became a racecar driver in Tokyo, and had an encounter with a UFO.
Heavy metal Mater -- UFM : unidentified flying Mater -- Tokyo Mater.
"3 Books in 1!"--Cover.
"A Mater's tall tales storybook"--Cover pages [4].
3.0
K-3
K-3.
Keywords: Automobiles -- Juvenile fiction; Automobiles -- Fiction